2010
DOI: 10.1590/s1984-29612010000200012
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Leishmania spp. em felinos do município de Araçatuba, SP

Abstract: ResumoEste trabalho teve como objetivo comparar a ocorrência de Leishmania spp. em gatos por dois métodos (citológico e sorológico), bem como associar a ocorrência deste protozoário com as variáveis sexo, idade e raça. Amostras séricas de 283 felinos domésticos foram testadas pela Reação de Imunofluorescência Indireta (RIFI), e o exame parasitológico direto de linfonodos também foi realizado para a verificação da positividade para Leishmania spp. Ocorrência de 0,7% (2/283) foi observada nos felinos examinados,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
1
5
0
3
Order By: Relevance
“…The other characteristics of the clinical lesions were similar to other reports of leishmaniasis in cats (Bonfante-Garrido et al, 1996;Souza et al, 2009;Trainor et al, 2010;Pennisi et al, 2015;Alves-Martin et al, 2017). There are reports that no clinical sign was observed in serologically positive felines (Costa et al, 2010;Bresciani et al, 2010;Alves-Martin et al, 2017). In other words, in cats, the symptomatology may present a similar course to the visceral leishmaniasis in dogs, going from apparently healthy animals, passing by oligosymptomatic, up to severe stages of the disease (Akhtardanesh et al, 2017;Gontijo & Melo, 2004).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The other characteristics of the clinical lesions were similar to other reports of leishmaniasis in cats (Bonfante-Garrido et al, 1996;Souza et al, 2009;Trainor et al, 2010;Pennisi et al, 2015;Alves-Martin et al, 2017). There are reports that no clinical sign was observed in serologically positive felines (Costa et al, 2010;Bresciani et al, 2010;Alves-Martin et al, 2017). In other words, in cats, the symptomatology may present a similar course to the visceral leishmaniasis in dogs, going from apparently healthy animals, passing by oligosymptomatic, up to severe stages of the disease (Akhtardanesh et al, 2017;Gontijo & Melo, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…The visualization of the amastigote forms of the aspirates of the lesions and/or lymph nodes was positive for the majority of the reports in symptomatic cats (Bonfante-Garrido et al, 1996;Souza et al, 2009;Bresciani et al, 2010;Sousa et al, 2019) and, as in the dogs, the lesions seem to be due to the immune response against the parasites (Hervás et al, 2001). However, the negative cytological test of the bone marrow, spleen and live has already been reported (Grevot et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The low number of cats seropositive for Leishmania spp. in comparison with dogs has been shown by other research groups (SOLANO-GALLEGO et al, 2007;BRESCIANI et al, 2010;SOBRINHO et al, 2012;CARDIA et al, 2013), and this can be attributed to the natural resistance of the cats against the protozoan, due to a more effective cellular immune response (SOLANO-GALLEGO et al, 2007). Moreover, the use of different methodologies and non-standardized protocols could also be responsible for these frequencies (SOLANO-GALLEGO et al, 2011).…”
Section: Introductionmentioning
confidence: 86%
“…In Brazil, studies on FeL using serological, parasitological, and molecular methods revealed that infection frequencies varied from 0% to 54% (BRESCIANI et al, 2010;VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SILVA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;MENDONÇA et al, 2017;COURA et al, 2018;MATOS et al, 2018). Only a small fraction of these studies was performed in the Northeast region that was home to 82.5% of all reported cases of human leishmaniasis in Brazil between 1980 and 2005, making this region an area of epidemiological relevance for this disease in Brazil (MAIA-ELKHOURY et al, 2008;SILVA et al, 2014;MENDONÇA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Neste mesmo trabalho pode-se afirmar que os gatos são infecciosos ao vetor e são mais propícios a infecção em áreas endêmicas a FVL foi confirmada através do xenodiagnóstico por Silva e colaboradores(2010).Os cães apresentam resposta humoral, nos gatos a resposta imune é celular, o que conferem a esta espécie um grau mais alto de resistência à infecção, o que pode justificar o pequeno número de gatos infectados e sintomáticos (COSTA et al,2010; NOÉ et al, 2015. Respostas imunológicas espécie específica proporcionam a proteção natural felina à infecção por Leishmania spp., são assintomáticos na ausência de outra doença ou estado de imunossupressão(Vides et al ;2011e Bresciani et al 2010Pennisi, 2015).…”
unclassified